The Influence Of Financial Literacy And Financial Behavior On Investment Decisions With Financial Technology As A Moderating Variable Among Generation Z - Evri Lala Sari; Hadi Paramu; Nurhayati (Cita konsultindo, 2025)
This study examines the effect of financial literacy and financial behavior on the investment decisions among Generation Z in Situbondo Regency. In addition, this research investigates the moderating role of financial technology on the relationship between financial literacy, financial behavior, and investment decisions of Generation Z. This research is explanatory research. The population in the study of all Generation Z individuals in Situbondo Regency. Using the snowball sampling method, a total of 309 respondents from Generation Z were obtained. The data were analyzed using Moderated Regression Analysis (MRA).The results of this study indicate that: (a) financial literacy and financial behavior significantly influence investment decisions among Generation Z, and (b) financial technology moderates and strengthens the relationship between financial literacy and financial behavior on investment decisions among Generation Z in Situbondo Regency.